2015
DOI: 10.1016/j.cj.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rice or wheat residue retention on the quality of milled japonica rice in a rice–wheat rotation system in China

Abstract: In rice-wheat rotation systems, crop straw is usually retained in the field at land preparation in every, or every other, season. We conducted a 3-year-6-season experiment in the middle-lower Yangtze River Valley to compare the grain qualities of rice under straw retained after single or double seasons per year. Four treatments were designed as: both wheat and rice straw retained (WR), only rice straw retained (R), only wheat straw retained (W), and no straw retained (CK). The varieties were Yangmai 16 wheat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…results of this experiment are generally consistent with this. In this experiment, we found that under the LFP ratio, although wheat straw returning was beneficial to improve the stickiness and the ratio of amylopectin content to amylose content, meanwhile, reduce the hardness and amylose content of the grain, it also reduced the gel consistency and taste value, which tended to deteriorate the taste quality of rice, this is basically the same as the research results of Liu et al (2007) and Hou et al (2015). The effect of the N application ratio on rice cooking and eating quality was also inconsistent.…”
Section: Coupling Effects Of Wheat Straw Returning and Basal N Fertil...supporting
confidence: 85%
“…results of this experiment are generally consistent with this. In this experiment, we found that under the LFP ratio, although wheat straw returning was beneficial to improve the stickiness and the ratio of amylopectin content to amylose content, meanwhile, reduce the hardness and amylose content of the grain, it also reduced the gel consistency and taste value, which tended to deteriorate the taste quality of rice, this is basically the same as the research results of Liu et al (2007) and Hou et al (2015). The effect of the N application ratio on rice cooking and eating quality was also inconsistent.…”
Section: Coupling Effects Of Wheat Straw Returning and Basal N Fertil...supporting
confidence: 85%
“…Paddy ( Oryza sativa L.) and wheat ( Triticum aestivum L.), widely cultured crops in the world, are considered as the most important staple foods in China ( Hou et al., 2015 ). Shanghai, the center of China’s economy and trade ( Wang and Zhang, 2005 ), imports most of its consumed wheat and paddy grains (approximately 80.0%) from other cities, such as Anhui, Shandong, and Heilongjiang.…”
Section: Introductionmentioning
confidence: 99%
“…Under hydroponic conditions, wheat absorbs much less Cd than rice [31]. The cultivation of soils previously passivated to reduce heavy metals with rice and wheat can reduce the amount of passivator needed to reduce the Cd content of wheat grains [32], improve the yield and nutrient content of rice and wheat grains [33,34], and maintain soil health [35,36]. The passivator needs to be used before the base fertilizer is applied.…”
Section: Introductionmentioning
confidence: 99%